Journey on the James : Three Weeks through the Heart of Virginia - Swift, Earl, 1958- (Book collections on Project MUSE., 2001)
From its beginnings as a trickle of icy water in Virginia's northwest corner to its miles-wide mouth at Hampton Roads, the James River has witnessed more recorded history than any other feature of the American landscape--as home to the continent's first successful English settlement, highway for Native Americans and early colonists, battleground in the Revolution and the Civil War, and birthplace of America's twentieth-century navy. In 1998, restless in his job as a reporter for the Norfolk Virginian-Pilot, Earl Swift landed an assignment traveling the entire length of the James. Reinforced by Pilot photographer Ian Martin and a lot of freeze-dried food and beer, Swift set out to immerse himself--he hoped not literally--in the river and its history. What Swift survived to bring us is this engrossing chronicle of three weeks in a fourteen- foot plastic canoe and four hundred years in the life of Virginia. Fueled by humor and a dauntless curiosity about the land, buildings, and people on the banks, and anchored by his sidekick Martin--whose photographs accompany the text- Swift endures dunkings, wolf spiders, near-arrest, channel fever, and twenty-knot winds, eventually making it to the Chesapeake Bay.